Pelargonium Extract EPs 7630 in the Treatment of Human Corona Virus-Associated Acute Respiratory Tract Infections – A Secondary Subgroup-Analysis of an Open-Label, Uncontrolled Clinical Trial - Keck, Tilman; Strobl, Andreas; Weinhaeusel, Andreas; Funk, Petra; Michaelis, Martin (Frontiers in Pharmacology, 2021)
Background: Experience in treating human coronavirus (HCoV) infections might help to identify effective compounds against novel coronaviruses. We therefore performed a secondary subgroup-analysis of data from an open-label, uncontrolled clinical trial published in 2015 investigating the proanthocyanidin-rich Pelargonium sidoides extract EPs 7630 in patients with the common cold. Methods: 120 patients with common cold and at least 2 out of 10 common cold symptoms received one film-coated 20 mg tablet EPs 7630 thrice daily for 10 days in an uncontrolled, interventional multicentre trial (ISRCTN65790556). At baseline, viral nucleic acids were detected by polymerase chain reaction. Common cold-associated symptoms and treatment satisfaction were evaluated after 5 days and at treatment end. Based on the data of patients with proof of viral nucleic acids, we compared the course of the disease in patients with or without HCoV infection. Results: In 61 patients, viral nucleic acids were detected. Of these, 23 (37.7%) were tested positive for at least one HCoV (HCoV subset) and 38 (62.3%) for other viruses only (non-HCoV subset). Patients of both subsets showed a significant improvement of common cold symptoms already after 5 days of treatment, although the observed change tended to be more pronounced in the HCoV subset. At treatment end, more than 80% of patients of both groups were completely recovered or majorly improved. In both subsets, less than 22% of patients took concomitant paracetamol for antipyresis. The mean number of patients’ days off work or school/college was similar (0.9 ± 2.6 days in HCoV subset vs 1.3 ± 2.8 days in non-HCoV subset). In both groups, most patients were satisfied or very satisfied with EPs 7630 treatment. Conclusion: EPs 7630 treatment outcomes of common cold patients with confirmed HCoV infection were as favourable as in patients with other viral infections. As this trial was conducted before the pandemic, there is currently no evidence from clinical trials for the efficacy of EPs 7630 in patients with SARS-CoV-2 infection. Dedicated non-clinical studies and clinical trials are required to elucidate the potential of EPs 7630 in the early treatment of HCoV infections.